2016
DOI: 10.1111/cns.12606
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Paxillin Correlates with Tumor Progression and Predicts Poor Survival in Glioblastoma

Abstract: SUMMARYAims: To explore the prognostic and clinicopathological features of glioma with Paxillin (PXN) expression based on a large number of samples. Methods: RNA sequencing data of 325 glioma samples from Chinese Glioma Genome Atlas (CGGA) database were obtained as discovery set. Three additional datasets were further obtained as validation sets. The protein expression pattern of PXN in glioma was measured by IHC. Kaplan-Meier survival and multivariate Cox analysis were used to estimate the survival distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…Our genetic data also indicate that Pxn is a downstream target of Ccnd1‐Cdk4 in human GBM cells. Interestingly, Pxn seems to behave as an oncogene in glioma progression and its overexpression is associated with high‐grade gliomas . Also, a positive correlation between GBM invasiveness and Pxn phosphorylation at tyrosine 118 has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Our genetic data also indicate that Pxn is a downstream target of Ccnd1‐Cdk4 in human GBM cells. Interestingly, Pxn seems to behave as an oncogene in glioma progression and its overexpression is associated with high‐grade gliomas . Also, a positive correlation between GBM invasiveness and Pxn phosphorylation at tyrosine 118 has been reported .…”
Section: Discussionmentioning
confidence: 99%
“…In the GBM cell line u87, super enhancers targeting CCND1 , CDK6 , EGFR , JUN , MET , MYC , NOTCH2 and RUNX1 have been identified [ 23 ]. In our study, super enhancer targets marked by 5hmC in common between IDH1 mt and IDH1 wt tumors and previously implicated in gliomagenesis included EGFR , MYC , CDK6 , NOTCH2 , RUNX1 , PDGFRB , PXN , ID3 , IGF1R , NEDD9 , and MSI2 [ 13 , 27 , 34 , 42 , 50 , 58 , 64 ]. Additional IDH1 wt super-enhancers marked by 5hmC in our dataset and implicated in GBM pathogenesis included WDR1 , TGFBI and PVT1 [ 11 , 36 , 43 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, glioblastoma multiforme (GBM), the most common and malignant type of glioma, remains one of the most lethal cancers in the central nervous system (CNS). Recent studies have demonstrated that the overexpression of paxillin at the RNA and protein level is associated with GBM tumor malignancy and hence, predictive of poor survival [ 107 ]. These data identify paxillin as a novel prognostic biomarker with potential anti-invasion therapeutic implications in GBM.…”
Section: Paxillin In Pathological Conditionsmentioning
confidence: 99%